2016
DOI: 10.1111/wrr.12465
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles production by two soil isolated bacteria, Bacillus thuringiensis and Enterobacter cloacae, and assessment of their cytotoxicity and wound healing effect in rats

Abstract: Production of silver nanoparticles by Bacillus thuringiensis and Enterobacter cloacae was performed and confirmed through UV-visible spectrophotometry, transmission electron microscopy (TEM), and x-ray diffraction (XRD) analyses. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay using mouse fibroblast cell line NIH-3T3 D4 was carried out and IC of AgNPs were obtained. The nontoxic dose of each AgNPs solution was selected for wound healing assay. Thirty-two rats were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The tested substances were first sterilized using the tyndallization method as microbial contaminations can interfere with the results of the MTT test. The tyndallization method is easy, safe, and free of adverse effects on the tested materials (Pourali et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The tested substances were first sterilized using the tyndallization method as microbial contaminations can interfere with the results of the MTT test. The tyndallization method is easy, safe, and free of adverse effects on the tested materials (Pourali et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the optical densities (ODs) of the wells were measured at 570 nm using enzyme‐linked immunosorbent assay reader. This assay was repeated three times and the IC 50 of each sample was calculated based on the following formula (Pourali et al, ; Pourali, Razavian Zadeh, & Yahyaei, ):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By analyzing bacterial growth and cytokine profiles in wound sections, the authors demonstrated the antimicrobial and anti-inflammatory potential of Ag NPs. Microbially synthesized Ag NPs enhanced wound-healing efficiacy in rats (11, 27, 28). Using a transforming growth factor (TGF)-β receptor inhibitor, Li and coworkers proposed the activation of the TGF-β1/Smad signaling pathway as a mechanism of wound-healing enhancement by polyvinylalcohol/chitosan oligosaccharide Ag nanofibers (29).…”
Section: Wound Healingmentioning
confidence: 99%